Free – bass accordion in modern educational systems - Algin, Sergei (ARTS AND MUSIC IN CULTURAL DISCOURSE. Proceedings of the International Scientific and Practical Conference, 2012)
The purpose of the work – to prove the advantages of the introduction of accordion with system of Kravtsov in modern educational systems. Are used practical methods. Conclusion: The accordion with a system of Kravtsov anticipates an interesting perspective in piano accordion – bayan culture and education.